Zinc ion battery electrolyte and preparation method and application thereof
By adding coumarin derivatives to the zinc ion battery electrolyte, the electrochemical performance problems of zinc ion battery in low temperature environments are solved, and the reversibility and cycle stability of zinc anode are significantly improved, ensuring that the battery is under different temperature conditions. Excellent performance.
Patent Information
- Application Number
- CN202411646795.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-31
AI Technical Summary
Water-based zinc ion batteries have difficulties in high reversibility and low-temperature performance. The zinc anode is prone to dendrites, resulting in battery cycle stability and safety problems, and the battery performance is significantly reduced under low-temperature conditions.
By adding coumarin derivatives to the zinc ion battery electrolyte, ultrasonic dissolving zinc salts in organic solvents to prepare the electrolyte solution to form a stable protective layer, optimize the deposition and electrochemical activity of zinc ions, improve the cycle stability of the battery and Energy efficiency.
It significantly reduces the formation of dendrites, improves the reversibility and cycle stability of zinc anode, ensures that the battery exhibits excellent electrochemical performance under different temperature conditions, extends the service life of the battery, and maintains stability in low temperature environments.
Smart Images

Figure CN119230977A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion battery electrolytes, and in particular relates to a zinc ion battery electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) dominate the fields of portable electronic devices and electric / hybrid vehicles due to their superior energy density and long cycle life. However, the limited resources, high cost, and potential safety hazards of lithium have restricted their further development in larger-scale energy storage applications. As alternatives, sodium-ion batteries (SIBs) and potassium-ion batteries (KIBs), despite their abundant resources and low cost, have relatively low energy density, high operating costs, and more serious safety issues, such as greater susceptibility to explosion, which limit their potential in future large-scale energy storage applications.
[0003] Therefore, researchers are exploring new battery technologies with low cost, high safety and long cycle life. Aqueous zinc-ion batteries (ZIBs) have become a hot topic of research due to their unique advantages. Metallic zinc has high theoretical weight and volume capacity, low redox potential, and shows good stability in water compared to lithium, sodium and potassium. In addition, the low cost and natural abundance of zinc are also important advantages as a battery material.
[0004] Although aqueous zinc-ion batteries (ZIBs) have many theoretical advantages, they still face some challenges in practical applications. In particular, ZIBs have significant difficulties in terms of high reversibility and low-temperature performance. The zinc anode is prone to produce dendrites during the charge and discharge process, which not only affects the cycle stability of the battery, but may also cause battery short circuits and safety issues. In addition, the poor reversibility of the zinc anode is also an urgent problem to be solved, which limits the long-term operation and energy efficiency of the battery. Under low temperature conditions, the mobility of zinc ions decreases and the conductivity of the electrolyte decreases, resulting in a significant decrease in battery performance, which limits the application of ZIBs in extreme climate conditions.
[0005] To solve these problems, researchers have tried to improve the performance of zinc anodes by adding electrolyte additives. These additives can change the solvation structure, regulate the deposition mode of zinc, and build a protective layer on the electrode surface, thereby improving the cycle stability and coulombic efficiency of the battery. However, although some studies have reported the positive effects of electrolyte additives, the specific mechanism of action and the optimal formula of the additives still need further research and optimization. In addition, how to achieve large-scale production and application of additives, and how to balance cost and performance, are also problems that need to be solved in the current technological development. In particular, more innovations and breakthroughs are needed to improve the performance and reversibility of zinc anodes in low temperature environments. Summary of the invention
[0006] The object of the present invention is to provide a zinc ion battery electrolyte and a preparation method and application thereof, so as to solve the technical problem that the existing electrolyte is difficult to meet the electrochemical performance of aqueous zinc ion batteries (ZIBs) in a low temperature environment.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a zinc ion battery electrolyte, comprising the following steps: dissolving a zinc salt in an organic solvent to obtain a basic electrolyte; A coumarin derivative is added into a basic electrolyte and stirred to obtain a zinc ion battery electrolyte.
[0008] Furthermore, the method of dissolving the zinc salt in the organic solvent is ultrasonic dissolution; the time of the ultrasonic dissolution is 5 to 10 minutes.
[0009] Furthermore, the zinc salt is one of zinc tetrafluoroborate, zinc trifluoromethanesulfonate, zinc sulfate and zinc perchlorate.
[0010] Furthermore, the concentration of the basic electrolyte is 1~3M.
[0011] Furthermore, the organic solvent is one or more of methanol, ethanol, ethylene glycol, N,N-dimethylformamide, N,N-dimethylacetamide and acetonitrile.
[0012] Furthermore, the coumarin derivative is one of coumarin, isocoumarin, 4-hydroxycoumarin or 6-carboxycoumarin.
[0013] Furthermore, the structural formula of the coumarin derivative is: , , or .
[0014] Furthermore, in the zinc ion battery electrolyte, the concentration of the coumarin derivative is 0.03-0.3 mol / L.
[0015] The invention also discloses a zinc ion battery electrolyte prepared by the preparation method.
[0016] The invention also discloses application of the zinc ion battery electrolyte in a zinc ion battery.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a zinc ion battery electrolyte. By adding a coumarin derivative into a basic zinc salt solution, the uniform deposition of zinc ions can be promoted at a low temperature below -20°C, the formation of dendrites can be significantly reduced, and a stable protective layer can be formed on the surface of the zinc anode. The protective layer can not only maintain the high reversibility of the battery at room temperature, but also maintain its stability in a low temperature environment, thereby ensuring that the battery can exhibit excellent electrochemical performance under different temperature conditions, and solving the technical problem of the electrochemical performance of aqueous zinc ion batteries (ZIBs) in a low temperature environment.
[0018] Furthermore, by precisely controlling the chemical structure and concentration of coumarin derivatives, we can optimize their solubility and electrochemical activity in the electrolyte, further improving the cycle stability and energy efficiency of zinc-ion batteries over the full temperature range. The preparation method of this electrolyte additive is simple, low-cost, and has excellent environmental adaptability, providing new possibilities for the application of aqueous zinc-ion batteries under extreme climatic conditions.
[0019] The present invention also discloses an electrolyte prepared by the above-mentioned preparation method. The effect of the coumarin additive in the zinc ion battery can be analyzed by its zinc affinity. Coumarin contains oxygen atoms in its molecular structure, which enables it to form a strong coordination effect with zinc ions. During the charge and discharge process of the battery, this zinc affinity preferential adsorption behavior helps the uniform deposition of zinc ions on the electrode surface, thereby reducing the formation and growth of dendrites. This uniform deposition pattern helps to improve the coulombic efficiency and cycle stability of the battery, because the deposition and stripping process of zinc ions becomes more controllable, reducing the polarization and side reactions of the battery during the charge and discharge process. The preferential adsorption of coumarin on the electrode surface may also form a stable solid electrolyte interface (SEI) film, which can protect the electrode from the erosion of the electrolyte while allowing the rapid transmission of zinc ions. This protective effect helps to maintain the integrity of the electrode structure and prolong the service life of the battery. Therefore, the coumarin additive effectively improves the electrochemical performance of the zinc ion battery through its zinc affinity preferential adsorption characteristics, and improves the efficiency and cycle life of the battery.
[0020] The present invention also discloses the application of the electrolyte in a zinc ion battery. The electrolyte additive of the present invention can significantly improve the cycle stability of the battery. Relevant experimental results show that after hundreds of cycles, the capacity retention rate and coulombic efficiency of the battery are still maintained at a high level. This is due to the stable protective layer formed by the coumarin derivatives on the surface of the zinc anode, which effectively inhibits the growth of dendrites and the decomposition of the electrolyte.
[0021] Furthermore, in the LSV test, the electrolyte additive of the present invention can significantly increase the redox peak current of zinc ions, indicating that it enhances the electrochemical reaction kinetics of zinc ions on the electrode surface. This improved electrochemical reaction kinetics helps to improve the charge and discharge efficiency and power density of the battery; the CV test results show that the battery using the electrolyte of the present invention exhibits a more stable redox peak with a smaller peak separation, which indicates that the battery has higher reversibility and less polarization loss; the coumarin derivative additive helps the uniform deposition and dissolution of zinc ions on the electrode surface, thereby reducing the energy loss of the battery during the charge and discharge process. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The cycle life diagram of the zinc-copper asymmetric battery prepared with the electrolyte described in Comparative Example 1 and Example 1; Figure 2 The cycle life diagram of the zinc symmetrical battery prepared with the electrolyte described in Comparative Example 1 and Example 1; Figure 3 2 is a cycle life diagram of a zinc-copper asymmetric battery prepared using the electrolytes described in Comparative Example 2 and Example 2; Figure 4 The cycle life diagram of the zinc-copper asymmetric battery prepared with the electrolytes described in Comparative Example 3 and Example 3 under a -20° environment; Figure 5 The performance test diagram of the electrolyte described in Comparative Example 1 and Example 1; Among them: a-LSV curve; b-TAFEL curve; c-CV curve; Figure 6 The performance test diagram of the electrolyte described in Comparative Example 2 and Example 2; Among them: a-LSV curve; b-TAFEL curve; c-CV curve; Figure 7 It is a performance test diagram of the electrolyte described in Comparative Example 3 and Example 3; Among them: a-LSV curve; b-TAFEL curve; c-CV curve. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0025] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0026] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0027] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0028] The present invention provides a zinc ion battery electrolyte, which exhibits the following significant advantages in electrochemical performance tests: In the long cycle stability test, the electrolyte additive of the present invention can significantly improve the cycle stability of the battery. After hundreds of cycles, the capacity retention rate and coulombic efficiency of the battery are still maintained at a high level, thanks to the stable protective layer formed by the coumarin derivative on the surface of the zinc anode, which effectively inhibits the growth of dendrites and the decomposition of the electrolyte.
[0029] In the LSV test, the electrolyte additive of the present invention can significantly increase the redox peak current of zinc ions, indicating that it enhances the electrochemical reaction kinetics of zinc ions on the electrode surface. Such enhanced electrochemical reaction kinetics helps to improve the charge and discharge efficiency and power density of the battery.
[0030] The CV test results show that the battery using the electrolyte of the present invention exhibits more stable redox peaks with smaller peak separation, which indicates that the battery has higher reversibility and smaller polarization loss. The coumarin derivative additive helps the uniform deposition and dissolution of zinc ions on the electrode surface, thereby reducing the energy loss of the battery during the charge and discharge process.
[0031] The electrolyte additive of the present invention shows a lower corrosion current density and a more positive corrosion potential in the Tafel test, indicating that it can slow down the corrosion rate of the zinc anode and improve the corrosion resistance of the battery. This helps to extend the service life of the battery and maintain high performance in long-term operation.
[0032] The electrolyte additive of the present invention exhibits excellent electrochemical performance in LSV, CV, long cycle stability and Tafel tests, and the improvement of these performances directly reflects the remarkable effect of the additive in improving the reversibility, stability and energy efficiency of zinc ion batteries. Through the verification of these electrochemical tests, the present invention provides a solid technical foundation for the practical application and commercialization of aqueous zinc ion batteries.
[0033] The electrolyte additive disclosed in the present invention can effectively promote the uniform deposition of zinc ions under both normal and low temperature conditions, significantly reduce the formation of dendrites, and form a stable protective layer on the surface of the zinc anode. This protective layer can not only maintain the high reversibility of the battery at room temperature, but also maintain its stability under low temperature conditions, thereby ensuring that the battery can exhibit excellent electrochemical performance under different temperature conditions. By precisely controlling the chemical structure and concentration of coumarin derivatives, we can optimize their solubility and electrochemical activity in the electrolyte, and further improve the cycle stability and energy efficiency of zinc ion batteries over the entire temperature range. The preparation method of this electrolyte additive is simple, low-cost, and has excellent environmental adaptability, providing new possibilities for the application of aqueous zinc ion batteries under extreme climatic conditions.
[0034] The role of coumarin additives in zinc-ion batteries can be analyzed by their zinc affinity. Coumarin contains oxygen atoms in its molecular structure, which enables it to form a strong coordination with zinc ions. During the charge and discharge process of the battery, this zinc affinity preferential adsorption behavior helps the uniform deposition of zinc ions on the electrode surface, thereby reducing the formation and growth of dendrites. This uniform deposition pattern helps to improve the coulombic efficiency and cycle stability of the battery because the deposition and stripping process of zinc ions becomes more controllable, reducing the polarization and side reactions of the battery during charge and discharge.
[0035] In addition, the preferential adsorption of coumarin on the electrode surface may also form a stable solid electrolyte interface (SEI) film, which can protect the electrode from the erosion of the electrolyte while allowing the rapid transmission of zinc ions. This protective effect helps to maintain the integrity of the electrode structure and extend the service life of the battery. Therefore, coumarin additives effectively improve the electrochemical performance of zinc-ion batteries through their zinc-philic preferential adsorption characteristics, and increase the efficiency and cycle life of the battery.
[0036] Specifically, the electrolyte involved in the present invention is composed of the following components: 2 mol / L zinc tetrafluoroborate (Zn(BF4)2) as the main zinc salt, and 0.1 mol / L coumarin derivatives as electrolyte additives, dissolved in organic reagents such as methanol and ethanol; by precisely controlling the chemical structure and concentration of coumarin derivatives, we can optimize their solubility and electrochemical activity in the electrolyte, and further improve the cycle stability and energy efficiency of zinc-ion batteries over a wide temperature range.
[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0038] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0039] Example 1 A method for preparing a zinc ion battery electrolyte comprises the following steps: 0.7266 g of zinc tetrafluoroborate (Zn(BF4)2) was added to 1 mL of methanol solvent (MeOH), and the mixture was dissolved by ultrasonication in an ultrasonic machine until the solution was clear and transparent, thereby obtaining an electrolyte (basic electrolyte) with a concentration of 2 M (Zn(BF4)2) in MeOH. 0.1 M coumarin was added to the base electrolyte to obtain a zinc ion battery electrolyte (2B1X-MeOH).
[0040] Example 2 A method for preparing a zinc ion battery electrolyte comprises the following steps: 0.7266 g of zinc tetrafluoroborate (Zn(BF4)2) was added to 1 mL of ethanol solvent (ETOH) and dissolved by ultrasonication in an ultrasonic machine until the solution was clear and transparent to obtain an electrolyte (basic electrolyte) with a concentration of 2 M (Zn(BF4)2) in MeOH. 0.1 M coumarin was added to the base electrolyte to obtain a zinc ion battery electrolyte (2B1X-MeOH).
[0041] Example 3 A method for preparing a zinc ion battery electrolyte comprises the following steps: First, 0.5 mL of methanol solvent (MeOH) was drawn into a clean vial, and then 0.5 mL of N,N-dimethylformamide solvent (DMF) was drawn into the vial and mixed thoroughly; further, 0.7266 g of zinc tetrafluoroborate (Zn(BF4)2) was added to 1 mL of the mixed solution, and the solution was ultrasonically dissolved in an ultrasonic machine until the solution was clear and transparent, thereby obtaining an electrolyte (basic electrolyte) with a concentration of 2 M Zn(BF4)2in MeOH:DMF=1:1; 0.1 M coumarin was added to the basic electrolyte to obtain a zinc ion battery electrolyte (2B1X-ETOH).
[0042] Comparative Example 1 0.7266 g of zinc tetrafluoroborate (Zn(BF4)2) was added to 1 mL of methanol solvent (MeOH) and dissolved by ultrasonication in an ultrasonic machine until the solution was clear and transparent to obtain an electrolyte with a concentration of 2 M Zn(BF4)2in MeOH (basic electrolyte 2B0X-MeOH).
[0043] Comparative Example 2 0.7266 g of zinc tetrafluoroborate (Zn(BF4)2) was added to 1 mL of ethanol solvent (ETOH) and dissolved by ultrasonication in an ultrasonic machine until the solution was clear and transparent to obtain an electrolyte with a concentration of 2 M Zn(BF4)2in ETOH (basic electrolyte 2B0X-ETOH).
[0044] Comparative Example 3 0.5 mL of methanol solvent (MeOH) was drawn into a clean vial, and 0.5 mL of N,N-dimethylformamide solvent (DMF) was drawn into the vial and mixed thoroughly. 0.7266 g of zinc tetrafluoroborate (Zn(BF4)2) was further added to 1 mL of the mixed solution, and ultrasonically dissolved in an ultrasonic machine until the solution was clear and transparent, to obtain an electrolyte with a concentration of 2 M Zn(BF4)2in MeOH:DMF=1:1 (basic electrolyte 2B0X-1M1D).
[0045] Figure 1 The electrolytes were 2 M zinc tetrafluoroborate dissolved in methanol and 2 M zinc tetrafluoroborate and 0.1 M coumarin additive dissolved in methanol at 3.5 mA cm -2 Surface density, 3.5mAh cm -2The long cycle life diagram of zinc and copper based on surface capacity. It can be seen from the figure that compared with the electrolyte without coumarin additive, the use of the electrolyte proposed by the present invention not only improves the efficiency of zinc stripping and deposition (99.9%), but also increases the cycle life by more than three times (2400h).
[0046] Figure 2 The electrolytes were 2 M zinc tetrafluoroborate dissolved in methanol and 2 M zinc tetrafluoroborate and 0.1 M coumarin additive dissolved in methanol at 0.5 mA cm -2 Surface density, 1mAh cm -2 The surface capacity of the zinc symmetric battery cycle life diagram, it can be seen from the figure that compared with the electrolyte without coumarin additives, the use of the electrolyte proposed by the present invention not only increases the cycle life by more than three times (2400h), but also has a smaller polarization voltage (about 70mV).
[0047] Figure 3 The electrolytes were 2 M zinc tetrafluoroborate dissolved in ethanol and 2 M zinc tetrafluoroborate and 0.1 M coumarin additive dissolved in ethanol at 3.5 mA cm -2 Surface density, 3.5mAh cm -2 The long cycle life diagram of zinc and copper with respect to surface capacity shows that, compared with the electrolyte without coumarin additive, the electrolyte proposed by the present invention improves the stability of zinc stripping and deposition.
[0048] Figure 4 The zinc electrolyte was prepared by dissolving 2 m zinc tetrafluoroborate in a mixture of methanol and N,N-dimethylformamide in a weight ratio of 1:1 and adding 0.1 m coumarin additive to the mixture under low temperature of -20 °C and 3.5 mA cm -2 Surface density, 0.7 mAh cm -2 The long cycle life of zinc and copper with respect to surface capacity shows that compared with the electrolyte without coumarin additive, the electrolyte proposed by the present invention not only improves the efficiency of zinc stripping and deposition, but also improves the cycle life, indicating that coumarin can also improve battery performance at low temperatures.
[0049] Figure 5 The LSV curves, Tafel curves, and CV curves of the zinc electrolyte of 2 m zinc tetrafluoroborate dissolved in methanol and 2 m zinc tetrafluoroborate and 0.1 m coumarin additive dissolved in methanol are shown in Figure (a). It can be seen that the side reaction current of the electrolyte of the present invention at a voltage of -0.2 V is -2 mA, which is much smaller than -7 mA without additives. The addition of coumarin can inhibit the side reaction. It can be seen from Figure (b) that the electrolyte of the present invention has a small corrosion potential and a corrosion current of 0.0393 mA cm-1 at the same scan rate.-2 It is also much smaller than 0.2797 mA cm without additives. -2 , which also proves that the addition of coumarin can inhibit side reactions; from Figure (c), it can be seen that the overpotential is larger when the electrolyte of the present invention is used at the same scan rate, which proves that the addition of coumarin can form smaller and denser zinc crystal nuclei and make the deposition more uniform.
[0050] Figure 6 The LSV curves, Tafel curves, and CV curves of the zinc electrolyte of 2 m zinc tetrafluoroborate dissolved in ethanol and 2 m zinc tetrafluoroborate and 0.1 m coumarin additive dissolved in ethanol are shown in Figure (a). It can be seen that the side reaction current of the electrolyte of the present invention at a voltage of -0.2 V is -6 mA, which is much smaller than -8 mA without the additive. The addition of coumarin can inhibit the side reaction. It can be seen from Figure (b) that the electrolyte of the present invention has a small corrosion potential and a corrosion current of 0.0578 mA cm-1 at the same scan rate. -2 It is also much smaller than 0.0916 mA cm without additives. -2 , which also proves that the addition of coumarin can inhibit side reactions; from Figure (c), it can be seen that the overpotential is larger when the electrolyte of the present invention is used at the same scan rate, which proves that the addition of coumarin can form smaller and denser zinc crystal nuclei and make the deposition more uniform.
[0051] Figure 7 LSV curves, Tafel curves, and CV curves of a zinc electrolyte prepared by dissolving 2 m zinc tetrafluoroborate in a mixed solution of methanol and N,N-dimethylformamide in a weight ratio of 1:1 and a zinc electrolyte prepared by adding 0.1 m coumarin additive. As shown in Figure (a), the side reaction current of the electrolyte of the present invention at a voltage of -0.2 V is -3 mA, which is much smaller than -7 mA without the additive. The addition of coumarin can inhibit the side reaction. As shown in Figure (b), the electrolyte of the present invention has a small corrosion potential and a corrosion current of 0.0934 mA cm-1 at the same scanning rate. -2 It is also much smaller than 0.1428 mA cm without additives. -2 , which also proves that the addition of coumarin can inhibit side reactions; from Figure (c), it can be seen that the overpotential is larger when the electrolyte of the present invention is used at the same scan rate, which proves that the addition of coumarin can form smaller and denser zinc crystal nuclei and make the deposition more uniform.
[0052] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a zinc ion battery electrolyte, characterized in that: The following steps are involved: dissolving a zinc salt in an organic solvent to obtain a basic electrolyte; A coumarin derivative is added into a basic electrolyte and stirred to obtain a zinc ion battery electrolyte.
2. The method for preparing a zinc ion battery electrolyte according to claim 1, wherein The method of dissolving the zinc salt in the organic solvent is ultrasonic dissolution; the time of the ultrasonic dissolution is 5 to 10 minutes.
3. A method for preparing a zinc ion battery electrolyte according to claim 1, characterized in that, The zinc salt is one of zinc tetrafluoroborate, zinc trifluoromethanesulfonate, zinc sulfate and zinc perchlorate.
4. The method for preparing a zinc ion battery electrolyte according to claim 1, wherein The concentration of the basic electrolyte is 1-3M.
5. A method for preparing a zinc ion battery electrolyte according to claim 1, characterized in that, The organic solvent is one or more of methanol, ethanol, ethylene glycol, N,N-dimethylformamide, N,N-dimethylacetamide and acetonitrile.
6. A method for preparing a zinc ion battery electrolyte according to claim 1, characterized in that, The coumarin derivative is one of coumarin, isocoumarin, 4-hydroxycoumarin or 6-carboxycoumarin.
7. A method for preparing a zinc ion battery electrolyte according to claim 6, characterized in that, The structural formula of the coumarin derivative is: , , or .
8. A method for preparing a zinc ion battery electrolyte according to claim 1, characterized in that, In the zinc ion battery electrolyte, the concentration of the coumarin derivative is 0.03-0.3 mol / L.
9. A zinc ion battery electrolyte, characterized in that: The method is prepared by any one of claims 1 to 6.
10. Use of the zinc ion battery electrolyte according to claim 9 in a zinc ion battery.
Citation Information
Cited By
Aqueous zinc ion battery functional electrolyte additive and preparation method of aqueous zinc ion battery
CN119481361A
Application of an additive in aqueous zinc ion battery electrolyte and preparation method thereof
CN119481361B
